Constraining crustal velocity fields with InSAR for Eastern Turkey: Limits to the block‐like behavior of Eastern Anatolia. Issue 6 (20th June 2014) - Walters, R. J.; Parsons, B.; Wright, T. J.
Abstract The Sentinel‐1 satellite mission will enable global strain rate mapping from interferometric synthetic aperture radar (InSAR) and GPS data, and methods to combine these data in velocity fields will become increasingly important. Here we use InSAR to measure interseismic deformation in Eastern Turkey, across a ∼250, 000 km2 area that spans the Arabia‐Eurasia plate boundary zone. From our InSAR data we first estimate slip rates and locking depths for the North and East Anatolian Faults (NAF and EAF) of 20 ± 3 mm/yr and ∼16 km and 11 ± 3 mm/yr and ∼16 km, respectively, but we also combine the InSAR data with existing GPS velocity measurements to construct high‐resolution velocity and strain rate fields across the region for the first time. We calculate 2‐D and 3‐D velocity fields and find that strain is mainly localized across the NAF and EAF and that there is negligible differential vertical motion across the Eastern Anatolian plateau. We also show that high‐resolution 2‐D strain rate fields can be calculated from InSAR alone, even in the absence of GPS data. We fit a block model to our velocity field and estimate slip rates of ∼21 mm/yr and ∼8 mm/yr for the NAF and EAF, showing that our previous estimates differ from these values because they neglected crustal rotation. Although this rotation is an important component of the velocity field in Eastern Turkey, systematic residuals between our velocity field and the best fitting block for Anatolia suggest that the region is not block‐like as proposed by previous authors.